Impact of AI Tools on the Development of Expressive Language Skills of Children with Intellectual Disability at the Primary Level - N. Ilakkiya; V. Mrunalini (International Journal of Children, 2026)
Expressive language skills are important for everyone for an independent life. Human interaction is being forced to be replaced by technology. The impact of language skills of children is limited due to attention towards technology and artificial intelligence (AI) tools. This study aims to connect the AI tools like ChatGPT and Google AI Studio to develop the expressive language skills of children with mild to moderate intellectual disability. A quasi-experimental study design was employed, consisting of an intervention group (n=10) and a control group (n=10), which included both a pre-test and a post-test. The Madras Developmental Programming System was used before and after the intervention. The study results were significant with p < 0.05. The skills, like learning object names, narrating simple stories and jokes, and developing conversation, were developed. The limitations and future works are also discussed.
Keywords: AI tools; MDPS; expressive language; intellectual disability; language skills; technology